2016
DOI: 10.35362/rie71219
|View full text |Cite
|
Sign up to set email alerts
|

La ansiedad como variable predictora de la autoestima en adolescentes y su influencia en el proceso educativo y en la comunicación

Abstract: Este estudio pretende identificar la relación existente entre la ansiedad y la autoestima en una muestra de 207 adolescentes de 12-18 años, debido a la problemática presente en los Institutos de Educación Secundaria donde situaciones de ansiedad se producen diariamente, dificultando la comunicación entre alumnos y profesores, así como el desarrollo del currículo de un modo normalizado (Suárez Valdés y Pérez Pérez, 2012). Los factores estudiados son los siguientes: variables sociodemográficas como el género y e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
(6 reference statements)
1
1
0
2
Order By: Relevance
“…With regard to app addiction, our students showed very similar scores when compared to the results and similar scores for emotional investment, time management, and performance, and IA when compared with the results of the sample (also Spanish) [27,69]. As regards self-esteem, our students showed worse self-esteem compared to the Spanish sample, and, comparing our results with those with a sample of 136 students from the same university, the young people in this research showed greater levels of somatisation, depression, anxiety, and psychological distress than students from the same university two years ago [64,70]. Furthermore, possible gender differences were studied, showing that males in our sample presented more difficulties with planning (impulsiveness questionnaire BIS-11) than females.…”
Section: Discussionsupporting
confidence: 41%
See 1 more Smart Citation
“…With regard to app addiction, our students showed very similar scores when compared to the results and similar scores for emotional investment, time management, and performance, and IA when compared with the results of the sample (also Spanish) [27,69]. As regards self-esteem, our students showed worse self-esteem compared to the Spanish sample, and, comparing our results with those with a sample of 136 students from the same university, the young people in this research showed greater levels of somatisation, depression, anxiety, and psychological distress than students from the same university two years ago [64,70]. Furthermore, possible gender differences were studied, showing that males in our sample presented more difficulties with planning (impulsiveness questionnaire BIS-11) than females.…”
Section: Discussionsupporting
confidence: 41%
“…(e) Rosenberg Self-Esteem Scale (RSES) [63]. This is one of the most widely used scales in the assessment of self-esteem, particularly in adolescents [64]. It is a 10-item unidimensional instrument that assesses self-perception, feelings, and self-worth related to self-respect and self-acceptance.…”
Section: Instrumentsmentioning
confidence: 99%
“…Respecto a la otra variable de estudio se encontraron con un mayor nivel en los rangos de medio y bajo en las relaciones intrafamiliares, esto significa que los adolescentes que participaron en la presente investigación tienen un vínculo familiar aceptable. En una investigación planteada en Bolivia se expresa que la disfunción familiar puede crear problemas en el educación, conducta agresiva y dificultad de vinculación (Núñez y Crismán, 2016;Pairumani, 2017). De la misma manera, en un estudio ejecutado en México se conoció que la satisfacción vital se encuentra relacionada con las relaciones intrafamiliares tomando en cuenta el contacto, miembros, cercanía, apoyo, entre otros (Barraza, 2021).…”
Section: Discussionunclassified
“…Números estudios han encontrado una relación entre la ansiedad y depresión, algunos concluyen que aproximadamente el 50% de las personas que padecen depresión suelen presentar adicionalmente un trastorno de ansiedad (de Graaf, Bijl, Spijker, Beekman, & Vollebergh, 2003;Hek et al, 2011;Lamers et al, 2011;Regier, Rae, Narrow, Kaelber, & Schatzberg, 1998), e incluso algunos otros autores han concluido que conllevan una relación bidireccional entre sí (Jacobson & Newman, 2017). Mientras que, en el caso de la autoestima, se ha encontrado que entre mayor nivel haya en este constructo; será menor el nivel de ansiedad y depresión (Canto Pech & Castro Rena, 2004;Caballo et al, 2018;Hernández Prados, Belmonte García & Martínez Andreo, 2018;Núñez Vázquez & Crismán Pérez, 2016;Ortiz Garzón et al, 2014). A pesar de que las causas de la sintomatología ansiosa y depresiva son multifactoriales, los factores relacionados a la familia podrían actuar como desencadenantes o mantenedores de estos trastornos (Vargas Murga, 2014), principalmente lo referente a la unión y comunicación familiar (Álvarez Zúñiga et al, 2009;Flores-Pacheco et al, 2011).…”
unclassified